A new type of Maxwell stress in soft materials due to quantum mechanical-elasticity coupling. (February 2016) - Li, Xiaobao; Liu, Liping; Sharma, Pradeep
Abstract: All dielectrics deform when subjected to an electric field. This behavior is attributed to the so-called Maxwell stress and the origins of this phenomenon can be traced to geometric deformation nonlinearities. In particular, the deformation is large when the dielectric is elastically soft (e.g. elastomer) and negligible for most "hard" materials. In this work, we develop a theoretical framework which shows that a striking analog of the electrostatic Maxwell stress also exists in the context of quantum mechanical-elasticity coupling. The newly derived quantum-elastic Maxwell stress is found to be significant for soft nanoscale structures (such as the DNA) and underscores a fresh perspective on the mechanics and physics of polarons. We discuss potential applications of the concept for soft nano-actuators and sensors and the relevance for the interpretation of opto-electronic properties.